2017
DOI: 10.1038/ncomms14813
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free reconstitution reveals centriole cartwheel assembly mechanisms

Abstract: How cellular organelles assemble is a fundamental question in biology. The centriole organelle organizes around a nine-fold symmetrical cartwheel structure typically ∼100 nm high comprising a stack of rings that each accommodates nine homodimers of SAS-6 proteins. Whether nine-fold symmetrical ring-like assemblies of SAS-6 proteins harbour more peripheral cartwheel elements is unclear. Furthermore, the mechanisms governing ring stacking are not known. Here we develop a cell-free reconstitution system for core … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(117 citation statements)
references
References 29 publications
3
113
0
1
Order By: Relevance
“…In vitro , SAS-6 can oligomerize into structures closely resembling the cartwheel hub, suggesting that SAS-6 may impart the typical nine-fold symmetry to centrioles 2123 . However, the assembly of stable cartwheels in vivo likely requires additional proteins, interactions with the microtubule wall and/or preexisting centrioles 24,25 .…”
Section: Centrosome Structure and Assemblymentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro , SAS-6 can oligomerize into structures closely resembling the cartwheel hub, suggesting that SAS-6 may impart the typical nine-fold symmetry to centrioles 2123 . However, the assembly of stable cartwheels in vivo likely requires additional proteins, interactions with the microtubule wall and/or preexisting centrioles 24,25 .…”
Section: Centrosome Structure and Assemblymentioning
confidence: 99%
“…The conserved centriole duplication factor STIL (Ana2 in Drosophila ), interacts with SAS-6 and plays a central role in promoting SAS-6 recruitment and/or assembly 2632 . In Chlamydomonas , cartwheel formation requires the protein Bld10p 19,33 , which interacts with SAS-6 to relieve an inhibitory action of the SAS-6 C-terminus on cartwheel assembly 23 . In human cells, the putative Bld10p homolog CEP135, also interacts with hSAS-6 34 , but most CEP135 localizes to the parent centriole and not the procentriole 35,36 , suggesting additional roles in centriole biogenesis and PCM assembly.…”
Section: Centrosome Structure and Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…How distinct cartwheel elements and associated structures are organized during organelle assembly remains largely an open question. However, some clues came from a recent analysis using cryo‐ET of isolated Chlamydomonas procentrioles, which could be divided into three regions. First, a most proximal region that harbors only a cartwheel and no pinhead or microtubules; such a core cartwheel is characterized by two densities termed D1 and D2 (Figure ).…”
Section: The Native Cartwheelmentioning
confidence: 99%
“…[46,47] and C. reinhardtii [48] centrioles revealed that the spokes of successive SAS-6 rings merge as they radiate outwards, leading to stacking of SAS-6 rings with a periodicity of approximately 8.5 nm at the central hub and 17 nm at the end of spokes ( Figure 6A). SAS-6 stacking periodicity aligns with the axial periodicity of microtubules at the outer centriole wall.…”
Section: Discussionmentioning
confidence: 99%